Próteses parciais removíveis associadas a encaixes: implicações clínicas e laboratoriais - Reis, José Maurício dos Santos Nunes [UNESP]; Jorge, Bruna Maria de Oliveira [UNESP]; Alfenas, Bruna Fernandes Moreira [UNESP]; Abi-Rached, Filipe de Oliveira [UNESP]; Pavarina, Ana Cláudia [UNESP] (My University, 2013)
Nowadays, the fixed partial dentures and/or dental implants is the most requested treatmentby the majority of partially edentulous patients. However, depending on the periodontal condition of the remaining teeth, as well as the bone condition of the prosthetic space, the oral rehabilitation with these treatments may be limited or even contraindicated. In such cases, the use of removable partial dentures associated to attachments becomes an important alternative for aesthetic and functional rehabilitation. Attachments are mechanical devices consisted of two parts (patrix-matrix), one placed inside another, which act as direct retainer, providing retention, support and stability to the dentures. These devices can be classified as intra or extracoronal attachments, considering their position in relation to the abutment tooth. However, regardless the type of attachment, the association between fixed and removable partial dentures should be performed respecting the biomechanical principles of both. Therefore, the purpose of this study was to review and discuss the literature about the clinical and laboratory implications of the association between fixed and removable partial dentures by means of attachments.

Atualmente, a utilização de próteses fixas e/ou implantes osseointegrados é o tratamento almejado pela maioria dos pacientes parcialmente edêntulos. No entanto, dependendo da condição periodontal dos dentes remanescentes, bem como da condição óssea do espaço protético, a reabilitação oral com esses tratamentos torna-se limitada ou contraindicada. Nesses casos, a utilização de próteses parciais removíveis com encaixes torna-se importante alternativa para a reabilitação estética e funcional. Os encaixes são dispositivos mecânicos compostos por duas partes (macho-fêmea), uma situada internamente em relação à outra, que atuam como retentor direto, propiciando retenção, suporte e estabilidade às próteses dentárias. Esses dispositivos podem ser classificados como intra ou extracoronários, considerando o seu posicionamento em relação ao dente pilar. No entanto, independentemente do tipo de encaixe selecionado, a associação entre as próteses parciais fixa e removível deve ser realizada respeitando-se os princípios biomecânicos de ambas. Sendo assim, o objetivo deste estudo foi revisar e discutir a literatura quanto às implicações clínicas e laboratoriais da associação entre próteses parciais fixas e removíveis por intermédio de encaixes.
Removable partial dentures associated to attachments: clinical and laboratory implications
Keywords: Removable partial denture; Extracoronal attachment; Intracoronal attachment; Biomechanics; Continuity of patient care; Prótese parcial removível; Encaixe extracoronário; Encaixe intracoronário; Biomecânica; Continuidade da assistência ao paciente